Do demographic changes affect risk premiums? Evidence from international data - Andrew Ang; Angela Maddaloni (European Central Bank (ECB), 2003)
We examine the link between equity risk premiums and demographic changes using a very long sample over the whole twentieth century for the US, Japan, UK, Germany and France, and a shorter sample covering the last third of the twentieth century for fifteen countries. We find that demographic variables significantly predict excess returns internationally. However, the demographic predictability found in the US by past studies for the average age of the population does not extend to other countries. Pooling international data, we find that, on average, faster growth in the fraction of retired persons significantly decreases risk premiums. This demographic predictability of risk premiums is stronger for countries with well-developed social security systems and lesser-developed financial markets.
Keywords: G12; G15; J10; P46; 330; demography; international predictability; Population aging; risk premiums; social security